Polyseme Selection, Lemma Selection and Article Selection - Bergenholtz, Henning; Gouws, Rufus H. (Lexikos, 2017)
In linguistics, more specifically in the field of lexical semantics, a lot of attention has been given to polysemy and homonymy. The identification of and distinction between polysemy and homonymy should not be regarded as unproblematic. The lexicographic practice has traditional ways of presenting and treating polysemy and homonymy. This paper focuses on approaches in both linguistics and lexicography to polysemy and homonymy. Examples from the lexicographic practice are given. It is then shown that that the traditional lexicographic presentation and treatment of homonymy and polysemy in dictionaries with a text reception function, does not really assist the users adequately in their search to find the appropriate meaning of an unfamiliar linguistic expression. It is shown that different dictionaries often have the same lemma selection but not the same selection of polysemes. It is important that a dictionary should correctly coordinate a meaning and a specific linguistic expression. Consequently, a new approach is suggested for the presentation and treatment of homonymy and polysemy. Negotiating criticism expressed in both linguistics and lexicography, it is proposed that the lexicographic practice, in the case of dictionaries for text reception, should abolish the traditional distinction between homonyms as well as the presentation of the different senses of a polysemous word in a single article. Each meaning, whether the only meaning of a lexical item or one of any number of different senses, should be the only item giving the meaning in an article.